Editorial - Hiremath, Shobha Rani R. (Indian Journal of Pharmacy Practice)
Dear Readers Spurious and sub-standard medicines have raised a concern from patient groups and consumers due to media reports and lack of prompt regulatory intervention, which has created doubts and mistrust in the existing supply chain in the country. India is one of the leading countries in the world to manufacture and supply medicines globally to enable citizens to access quality medicines at the most affordable price. However, figures stated by the WHO have shockingly highlighted that 35% of the world’s spurious and sub-standard medicines are produced from manufacturers within India, accounting for about 20% of the total local pharmaceutical business. These spurious or sub-standard productions resemble their genuine counterparts so closely with the aid of sophisticated technology created by these “in” genuine manufacturers. This malpractice is so well shielded that it is challenging for even experts to identify the difference.